2012
DOI: 10.1111/j.1523-1739.2012.01828.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Data on Avian Demographics and Site Persistence during Overwintering to Assess Quality of Restored Riparian Habitat

Abstract: Monitoring responses by birds to restoration of riparian vegetation is relatively cost-effective, but in most assessments species-specific abundances, not demography, are monitored. Data on birds collected during the nonbreeding season are particularly lacking. We captured birds in mist nets and resighted banded birds to estimate species richness and diversity, abundance, demographic indexes, and site-level persistence of permanent-resident and overwintering migrants in remnant and restored riparian sites in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…All data statistical analyses were performed by using SPSS v15.0 (SPSS, Inc., Chicago, IL). X 2 -Tests was used to compare CRP genotypes distribution within those predicted SNPs, Bonferroni correction was used in post-hoc test to correct for multiple testing (one genotype vs two other genotypes), with a new level of significance as 0.017[ 27 ]. The association between CRP SNPs and circulating CRP concentration was investigated and evaluated by using one-way ANOVA with tukey post hoc.…”
Section: Methodsmentioning
confidence: 99%
“…All data statistical analyses were performed by using SPSS v15.0 (SPSS, Inc., Chicago, IL). X 2 -Tests was used to compare CRP genotypes distribution within those predicted SNPs, Bonferroni correction was used in post-hoc test to correct for multiple testing (one genotype vs two other genotypes), with a new level of significance as 0.017[ 27 ]. The association between CRP SNPs and circulating CRP concentration was investigated and evaluated by using one-way ANOVA with tukey post hoc.…”
Section: Methodsmentioning
confidence: 99%
“…For example, in a South African agroecosystem, mango orchards complemented remnant natural habitats by providing vertical structure otherwise lacking in the landscape (Ehlers Smith et al 2015). Though the mango bird assemblage was not complementary, the orchards did harbor a subset of the species found in natural habitats (Ehlers Smith et al 2015), as we have found in our system (compare Appendix S2: Table S1 with Latta et al 2012, Dybala et al 2015.…”
Section: The Intermediate Landscape-complexity Hypothesismentioning
confidence: 48%
“…Nonterritorial species (i.e., those that flock, maintain a nonexclusive home range, or are transient) represent an additional overwintering strategy that needs further study as they display more complex movement patterns than individuals maintaining an exclusive territory. Density (Johnson, 2007) and site persistence (Latta, Howell, Dettling, & Cormier, 2012) are likely to be indicators of habitat quality for nonterritorial species. For example, differences in age/sex ratios between habitats can be the result of despotic distributions of highly territorial species (Fretwell & Lucas, 1970), and not likely relevant for nonterritorial species.…”
Section: Introductionmentioning
confidence: 99%
“…For example, differences in age/sex ratios between habitats can be the result of despotic distributions of highly territorial species (Fretwell & Lucas, 1970), and not likely relevant for nonterritorial species. Density (Johnson, 2007) and site persistence (Latta, Howell, Dettling, & Cormier, 2012) are likely to be indicators of habitat quality for nonterritorial species. Density can be a cue for resource availability (Stamps, 1991) and nonterritorial birds are more likely to move out of (i.e., not persist in) habitats that decline in quality over time compared to species that have invested time in establishing a territory.…”
Section: Introductionmentioning
confidence: 99%